World cricketers - Martin-Jenkins, Christopher (Oxford University Press, 1996)
This exhaustive work includes not only the biographical details of 2000 players who have won official test caps, but also the career details of all players of any significance since the dawn of the game. Entries are arranged alphabetically within sections on the nine test countries